Digital design : with a introduction to the verilog hdl - Mano, M. Morris , 1927-; Ciletti, Michael D. (Pearson Prentice Hall, 2013)
"Digital Design, "fifth edition is a modern update of the classic authoritative text on digital design. This book teaches the basic concepts of digital design in a clear, accessible manner. The book presents the basic tools for the design of digital circuits and provides procedures suitable for a variety of digital applications